(3TQM GdbUjOI GdNGbGfjIs - (3CHh OGhO SdjeGf Hf CHhGdbGSe MLGLs
(3ChdgG (B:s
(3gPG cJGH bUOfG ajg Edi TQM bUjOI CHh eRGMe ehSi GdeYQha HGdNGbGfj QMeg Gddg GdJj bGdgG aj GdbQGA hMSf GdBOGA s
(3BNQgG (B:s
(3hJHOC YfOdCfgG oehGNjI aj GdUhJ hGdLgQ aPcQJ GdHOd hGdYdg ajhSdc HfG WQjb ef eVi ef UGdMi SdafG s
(3Vef eLehY , JQJjHgG (B: (3ef U (B1 - (3U(B55s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3QhGjIs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs